TANGGUNG JAWAB WALI MEWAKILI ANAK DI BAWAH UMUR DALAM PENJUALAN HARTA WARISAN MENURUT HUKUM ISLAM (STUDI PUTUSAN NOMOR 0009/PDT.P/2014/PA.PAS) - WAN SHANYA CHALFINA BARUS (PREMISE LAW JURNAL, 2017)
After the parents of a child died, he is raised by his guardian, especially when he is still a minor. According to the Court Ruling No. 0009/Pdt.P/2014/PA.Pas, a mother can be selectedas the guardian for the minor the sell his property. The problems discussed in the research was the guardian's responsibility for the minor according to Islamic Laws, and the legal protection for the minor whose guardian neglects his responsibility according to Islamis Laws in the implementation of the Ruling No. 0009/Pdt.P/2014/PA.Pas.Keywords :